2018
DOI: 10.22456/2316-2171.74679
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Influentes No Estilo De Vida E Na Saúde Dos Idosos Brasileiros: Uma Revisão Integrativa

Abstract: O envelhecimento da população é uma realidade e diversos são os fatores que influenciam na saúde dos indivíduos que estão envelhecendo, como o estilo de vida, sendo um dos pontos mais importantes para se apresentar uma boa saúde. Verificado o envelhecimento populacional no Brasil e a grande influência do estilo de vida na saúde do idoso, foi realizada uma Revisão Integrativa no intuito de identificar quais os fatores que influenciam o estilo de vida dos idosos brasileiros e quais as consequências para sua saúd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…This result is consistent with other research of national representativeness (18) . This finding could be related to the lifestyle adopted by elderly individuals in these regions (27) , as well as to the higher life expectancy in the South of the country, increasing the period of exposures and susceptibility to the occurrence of two or more chronic health conditions, thus justifying the higher prevalences of the outcome observed in the Southern region (28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with other research of national representativeness (18) . This finding could be related to the lifestyle adopted by elderly individuals in these regions (27) , as well as to the higher life expectancy in the South of the country, increasing the period of exposures and susceptibility to the occurrence of two or more chronic health conditions, thus justifying the higher prevalences of the outcome observed in the Southern region (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to toxins, like nicotine, increases the incidence of cancer, chronic respiratory diseases, and others, in addition to multimorbidity (30) . Research has observed the potential role of smoking and the consumption of tobacco products, along with excessive alcohol consumption, in the occurrence of multimorbidity (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Esse resultado está em consonância com outras pesquisas de representatividade nacional (18) . Esse achado pode estar relacionado ao estilo de vida adotado pelas pessoas idosas dessas regiões (27) , bem como à maior expectativa de vida no Sul do país, o que aumenta o período de exposições e a suscetibilidade à ocorrência de duas ou mais condições crônicas de saúde, justificando assim as maiores prevalências do desfecho observadas na região Sul (28) .…”
Section: Discussionunclassified
“…A exposição a toxinas, como a nicotina, aumenta a incidência de câncer, doenças respiratórias crônicas, entre outras, além de multimorbidade (30) . Pesquisas vêm observando o potencial papel do tabagismo e consumo de derivados de tabaco, além do consumo abusivo de álcool, na ocorrência de multimorbidade (27) .…”
Section: Discussionunclassified
“…Nutritional assessment is part of the geriatric assessment, and malnutrition occurs often among older individuals [2]. Aging is associated with various physiological changes, which may have significant implications on the nutritional status of older individuals [3].…”
Section: Introductionmentioning
confidence: 99%